The German sickle cell disease registry reveals a surprising risk of acute splenic sequestration and an increased transfusion requirement in patients with compound heterozygous sickle cell disease HbS/β-thalassaemia and no or low HbA expression - Allard, Pierre Nicolas; Tagliaferri, Laura; Weru, Vivienn; Cario, Holger; Lobitz, Stephan; Grosse, Regine; Bleeke, Matthias; Oevermann, Lena; Hakimeh, Dani; Jarisch, Andrea; Kopp-Schneider, Annette; Kulozik, Andreas; et al. (European journal of haematology, 2024)
Patients with sickle cell disease (SCD) in Germany exhibit a substantial genetic diversity in the β-globin genotype. Data collected by the national German SCD registry reflect this diversity and allowed us to analyze the phenotypes associated with different SCD genotypes. Our study focused on 90 patients with HbS/β-thalassaemia (HbS/β-thal) and compared these to patients with HbSS and HbSC. Patients with HbS/β-thal were classified into three groups: HbS/β0-thal (no HbA), HbS/β+-thal (HbA < 14%), and HbS/β-thal (HbA≥14%). In comparison to HbSS, patients with HbS/β-thal had higher Hb-levels, lower hemolytic activity and rarely required red blood cell transfusions. HbS/β0-thal and HbS/β+-thal closely resembled each other and are jointly referred to as HbS/β0/+-thal. Compared to HbSS, patients with HbS/β0/+-thal experienced a similar frequency of vasoocclusive crises and degree of hemolysis. However, the frequency of red blood cell transfusions (0.6 vs. 0.39/year, p = .0049) and splenic sequestration crises (42.4 vs. 15.5% of patients, p = 3.799e-05) was higher in HbS/β0/+-thal than in HbSS, but close to zero in HbS/β-thal. In conclusion, the level of HbA expression determines the phenotype of HbS/β+-thal. HbS/β-thal expressing no or little HbA is hematologically similar to HbSS, but causes a previously unknown high risk of splenic sequestration.